Blockchain based sustainable energy transition of a Virtual Power Plant: Conceptual framework design & experimental implementation - A.M.A. Daiyan Kaif; Khandoker Shahjahan Alam; Sajal K. Das (Energy Reports, 2024)
Sustainable frameworks are being introduced by technological breakthroughs to address the continuously increasing demand for energy and this article presents a novel framework for a Virtual Power Plants to sustain and optimize Distributed Energy Resources (DERs) administration through blockchain technology. The multi-layered architecture integrates blockchain technology with other VPP components, such as a cloud service provider, grid and transmission operator, and forecasting of DERs, to optimize bidding and scheduling in real-time across multiple markets to enhance energy efficiency and grid stability. By employing a system engineering methodology, this framework incorporates smart meters to facilitate the transmission and reception of data i.e., voltage, and current between participants, and DERs within the network. This strategy makes it easier to advance sustainable energy sources, which advances predictive capabilities, strengthens the framework’s resilience, and protects the environment. The investigation of demand response, functional and system trade-off analysis, configuration selection, and other subsystems within a decentralized network offers insights into the necessary components and challenges involved in the construction of such a system. This study contributes comprehensive assistance and valuable insights to both practitioners and researchers involved in the field of sustainable energy transition through Virtual Power Plant.